Katharina Uhde, The Music of Joseph Joachim (2018) (Journal of the Society for Musicology in Ireland, 2019)
A review of Katharina Uhde, The Music of Joseph Joachim (Woodbridge: Boydell and Brewer, 2018). ISBN 978-1783272846